Awareness, knowledge and prevention of cervical cancer among female students from secondary schools in Kuala Terengganu, Terengganu - Abdul Ghafor, Fatin Syakirah (2016)
Cervical cancer is a cancer that occurs to the epithelial cells of the cervix. It is the secondary cause of female cancer after breast cancer. The study was conducted to observe the level of awareness, knowledge and prevention of cervical cancer take by the female students in Kuala Terengganu. A cross-sectional study had been done to 470 students. Out of 470, 438 questionnaires were returned completely. The data was collected by using a validated and self-administered questionnaire which included demographic data, awareness, knowledge and prevention of cervical cancer. In this study, the data were analysed by using a Statistical Package for Social Science (SPSS) version 22.0. It included descriptive analysis and Chi-square test. The data presented that 51.83 % was from PMR/PT3 level, 39.50 % from UPSR level and 8.68 % from SPM level aged 13 to 19 year-old. Majority of these students (90.9 %) had heard about cervical cancer. Out 438, 229 respondents got information about cervical cancer from mass media, which were television and radio. However, most of the students still had inadequate knowledge on risk factors and symptoms of cervical cancer. More than half of the students aware of HPV vaccination. It was because 79.5 % of them already vaccinated against HPV.